2020
DOI: 10.17221/47/2019-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

A breeding concept to improve the performance of locally cultivated bread wheat (Triticum aestivum L.) cultivars

Abstract: The objective of this study was to explore the internal variability in six established F7 commercial wheat cultivars for breeding purposes. They are sown traditionally in the region of Western Macedonia, Greece. Spikes of the six cultivars were sown in 2008 in separate rows. A head to row selection scheme was applied for two growing periods in order to select lines within the cultivars, based on various traits such as: the total spike number, the spike weight per row, the 1000-kernel weight and the specific we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In order to accumulate a desirable gene pool in improved wheat germplasm, it is necessary to comprehend the extent of genetic variation and the inheritance pattern of the measurable traits in relation to the targeted environment for which genotypes are to be developed (Fellahi et al, 2015). Wide spread commercial varieties contain valuable of internal variability which depicts that a selection within the varieties may be important for increasing the grain yield and other quantitative or qualitative traits (Greveniotis et al, 2020).…”
Section: Mean Values and Modes Of Inheritancementioning
confidence: 99%
“…In order to accumulate a desirable gene pool in improved wheat germplasm, it is necessary to comprehend the extent of genetic variation and the inheritance pattern of the measurable traits in relation to the targeted environment for which genotypes are to be developed (Fellahi et al, 2015). Wide spread commercial varieties contain valuable of internal variability which depicts that a selection within the varieties may be important for increasing the grain yield and other quantitative or qualitative traits (Greveniotis et al, 2020).…”
Section: Mean Values and Modes Of Inheritancementioning
confidence: 99%
“…The identification of genetic variability linked to molecular markers may aid breeders in achieving genetic gain and improving their breeding strategies (Voss-Fels et al, 2019;Singh et al, 2020). Molecular markers enable breeders to address diverse pragmatic goals, including enhancing agronomic features, developing resistance to diseases and pests, as well as elevating crop yields and their adaptation performance (Kong et al, 2005;Guo et al, 2015;Abdur Rehman Arif et al, 2023). Wheat genetic maps have been developed and expanded using various molecular markers, such as RFLP, AFLP, SSR, ISSR, and SNP (Röder et al, 1998;Bohn et al, 1999;Somers et al, 2004;Rimbert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation to specific local conditions plays the main role of the breeding program with the aim of providing a stable level of yield potential and quality parameters (Tishchenko et al, 2014). Long-term selection for a typical local environment ensures the appearance of unique alleles and the development of unique allele combinations (Greveniotis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2n = 2x = 14, DD) were selectively crossed to pass the elite genes of desirable traits to their progenies [2]. Consequently, SHW is a valuable source of genetic variability, with favorable traits, such as improved yield and abiotic and biotic stress tolerance, which are the primary targets of modern breeding strategies [3]. A previous study on genetic diversity in SHW has reported that this breed has higher levels of diverse amplified fragment length polymorphisms (39%) than common bread wheat (12-21%) [4].…”
Section: Introductionmentioning
confidence: 99%